2000
DOI: 10.1046/j.1440-6047.2000.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Tempe, a nutritious and healthy food from Indonesia

Abstract: Tempe is a fermented soy bean product originally made by Central Javanese people through fermentation with Rhizopus species. Although there is evidence of earlier fermentation of soy, tempe had appeared in the Central Javanese food pattern in the 1700s. Through its extensive use in main meals and snacks, it has led to people in the Jakarta prectinct having the highest known soy intake in the world and accordingly of the isoflavones contained. This provides an unique opportunity to consider the health effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
2
24

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(125 citation statements)
references
References 18 publications
4
95
2
24
Order By: Relevance
“…Perbedaan kadar air terjadi karena perbedaan penetrasi air ke dalam matriks biji dan perbedaan pengembangan biji. Kadar air tempe juga dipengaruhi oleh aktivitas pertumbuhan kapang dalam tempe (Astawan et al, 2013 4,0 3,5 4,0 3,5 4,0 3,0 Keterangan: 1) Menggunakan uji hedonik/ tingkat kesukaa skala 1-5, yaitu: 1=sangat tidak suka, 2=tidak suka, 3=agak suka; 4=suka, dan 5=sangat suka 2) Menggunakan uji skoring skala 1-5, yaitu: 1=sangat lunak, 2=lunak, 3=sedang, 4=keras, dan 5=sangat keras; diuji dibandingkan dengan kotiledon bijinya yang dapat disebabkan oleh hilangnya beberapa komponen terlarut seperti gula dan mineral dari biji kedelai (Bavia et al, 2012), aktivitas proteolitik miselium kapang (Rahayu 2004), dan peningkatan jumlah nitrogen terlarut dan asam amino bebas dalam tempe karena digunakan oleh kapang Rhizopus sebagai sumber N untuk pertumbuhannya (Astuti et al, 2000).…”
Section: Varietasunclassified
“…Perbedaan kadar air terjadi karena perbedaan penetrasi air ke dalam matriks biji dan perbedaan pengembangan biji. Kadar air tempe juga dipengaruhi oleh aktivitas pertumbuhan kapang dalam tempe (Astawan et al, 2013 4,0 3,5 4,0 3,5 4,0 3,0 Keterangan: 1) Menggunakan uji hedonik/ tingkat kesukaa skala 1-5, yaitu: 1=sangat tidak suka, 2=tidak suka, 3=agak suka; 4=suka, dan 5=sangat suka 2) Menggunakan uji skoring skala 1-5, yaitu: 1=sangat lunak, 2=lunak, 3=sedang, 4=keras, dan 5=sangat keras; diuji dibandingkan dengan kotiledon bijinya yang dapat disebabkan oleh hilangnya beberapa komponen terlarut seperti gula dan mineral dari biji kedelai (Bavia et al, 2012), aktivitas proteolitik miselium kapang (Rahayu 2004), dan peningkatan jumlah nitrogen terlarut dan asam amino bebas dalam tempe karena digunakan oleh kapang Rhizopus sebagai sumber N untuk pertumbuhannya (Astuti et al, 2000).…”
Section: Varietasunclassified
“…The fermentation process improves the nutritional value of tempeh by increasing the availability of isoflavone aglycones. These aglycones exist in smaller amounts in other nonfermented soy products such as tofu and soymilk (Wang & Murphy, 1994;Astuti & Dalais, 2000). Carrão-Panizzi et al (1998) studied the influence of the environment on the growth of Brazilian soybean cultivars and concluded that differences in the isoflavone content, in different sowing locations, allows the selection of locations for the production of soybean with low or high isoflavone contents.…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, tempe is consumed as a protein-rich meat substitute by all economic groups. Outside Indonesia, tempe gains interest as a major protein source other than meat (Astuti, 2000;Nout & Kiers, 2005;Steinkraus, 1996). Figure 1 shows soya bean tempe manufactured and sold in the Netherlands.…”
Section: Definitionmentioning
confidence: 99%
“…produces a variety of carbohydrases, lipases and proteases, which degrade the macronutrients into substances of lower molecular mass, with a higher water-solubility. Also vitamins, phytochemicals and anti-oxidative constituents are formed (Astuti, 2000;Nout & Kiers, 2005). Table 1 Whereas the change in total nitrogen content during fermentation is negligible, an increase of free amino acids takes place, due to hydrolysis of the proteins.…”
Section: Biochemical Changes Occurring During Fermentationmentioning
confidence: 99%